Bacillariophyceae de los canales de drenaje de Corfo (Río Colorado, Buenos Aires, Argentina) - Vouilloud, Amelia Alejandra Beatriz (2001)
Bacillariophyceae from the channels of CORFO (Colorado River, Buenos Aires. Argentina). This work is a contribution to the knowledge of the diatomaceous ﬂora from the drainage channels of brackish water of CORFO (Colorado River), located in the southern area of the province of Buenos Aires, Argentina. Ninety species were identified; seven of them belong to the order Centrales and the remaining eighty-three to the order Pennales. Cylindrotheca gracilis (Brébisson) Grunow and Nitzschia agnita Hustedt are new records for Argentina, while Hyalodiscus Ientiginosus John, Navicula circumtexta Meister, Plagiotropis lepidoptera (Pfitzer) Cleve, Nitzschia desertorum Hustedt, N. heuﬂen'ana Grunow, N. rautenbachiae Cholnoky, and N. reverse W. Smith are new records for Buenos Aires. This study includes a table showing the presence/absence of the identiﬁed taxa, as well as a description of the species which are either new or rare for Argentina and the province of Buenos Aires, or interesting because of their morphology and/or taxonomy.